Influence of Ink Viscosity on Dot Gain and Print Density in Flexography - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2012)
Flexo printing systems are mainly used in packaging applications. Substrates, anilox rolls, ink types, viscosity levels of inks, which are used in flexo printing systems have an effect on print density and dot area in printing. In the study, test printings were performed with the above parameters in IGT F1 test printing machine, printings were measured by densitometer and evaluations were made through the obtained data. A higher level of print density was achieved in printings made with solvent- and water-based inks on coated papers when compared to the printings made on uncoated papers. Higher levels of print density were obtained on uncoated papers with water-based inks and on coated papers with solvent-based inks. It was observed that dot area values were same in printings performed with water- and solvent-based inks of 17 viscosity level on coated and uncoated papers. Thus, viscosity value of ink should be 17 in printings to be performed with water- and solvent-based inks under optimum printing room conditions.
Keywords: Flexography; Flexo ink; Dot gain; Print quality; Print density